2020
DOI: 10.1103/physrevb.101.235163
|View full text |Cite
|
Sign up to set email alerts
|

Sharp peak of the critical current density in BaFe2xNixAs2 at optimal composition

Abstract: The importance of type-II superconductors with strong pinning comes from their ability to carry large electrical currents in the presence of a magnetic field. We report on the results of the bulk magnetization measurements in the superconducting state in high-quality single crystals of BaFe 2−x Ni x As 2 at various doping levels ranging from the underdoped to the overdoped regimes. The zero-temperature superconducting critical current density J c at optimal composition x = 0.10, where the superconducting trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 52 publications
3
6
0
Order By: Relevance
“…On the other hand, the lower values of jc(0)/jd 10 -3 -10 -2 are characteristic for high-temperature superconductors, e.g. the cuprate family, in which the Ginzburg-Landau parameter is large ( 100) and pinning originated from point defects, e.g., oxygen vacancies 52 , is relatively weak. To improve the infield critical current performance in cuprates, different types of artificial pinning centers are introduced in the sample structure.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the lower values of jc(0)/jd 10 -3 -10 -2 are characteristic for high-temperature superconductors, e.g. the cuprate family, in which the Ginzburg-Landau parameter is large ( 100) and pinning originated from point defects, e.g., oxygen vacancies 52 , is relatively weak. To improve the infield critical current performance in cuprates, different types of artificial pinning centers are introduced in the sample structure.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 5.10 shows the final product, and the central result of this chapter; a sharp peak in the critical current density of Ni-Ba122 occurring at the optimal doping value of x = 0.050. This result was published in Superconducting Science and Technology [141], and has since also been observed by other groups also measuring J c as a function of nickel doping [118].…”
Section: J C Versus Dopingsupporting
confidence: 73%
“…It is interesting to note that this peak is less prominent in the parallel field orientation, also coinciding with much smaller values of J c , with a peak value just over 0.1 MA/cm 2 . A number of studies in doped BaFe 2 As 2 single crystals have found that there is a coexistence of δl and δT c pinning [112,118,119] thus, this difference could be interpreted as each orientation having a dominant contribution from different pinning mechanisms, and the quantum critical behaviour is favouring improvement in one of the two.…”
Section: J C Versus Dopingmentioning
confidence: 99%
“…Similar results have been observed in other iron pnictide superconductors as reported in Refs. [18,60,61,62]. Moreover, according to Dew-Hughes model [57], h max < 0.5 indicates a δl pinning, while h max > 0.5 suggests δT c pinning, therefore, h max = 0.27 in present case is suggestive of δl pinning.…”
Section: Resultsmentioning
confidence: 51%